2018
DOI: 10.1186/s12936-018-2602-0
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Plasmodium falciparum haemozoin and l-arginine: implication for nitric oxide production

Abstract: BackgroundPlasmodium falciparum haemozoin, a detoxification product of digested haemoglobin from infected erythrocytes, is released into the bloodstream upon schizont rupture and accumulates in leukocytes. High levels of haemozoin correlate with disease severity. Some studies have shown that concentrations of the substrate of inducible nitric oxide synthase (iNOS), l-arginine, as well as nitric oxide are low in patients infected with P. falciparum malaria. The present study investigates, in vitro, the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…GCT were purified by magnetic separation using MACS columns (Miltenyi®), based on the paramagnetic properties of haemozoin, which is present in GCT. Cultures at ~ 0.5 % haematocrit were placed onto an LS column to retain and remove the free haemozoin, as described earlier [ 31 ]. The LS column elution, which contains GCT, was transferred onto an LD column, where GCT remained attached.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GCT were purified by magnetic separation using MACS columns (Miltenyi®), based on the paramagnetic properties of haemozoin, which is present in GCT. Cultures at ~ 0.5 % haematocrit were placed onto an LS column to retain and remove the free haemozoin, as described earlier [ 31 ]. The LS column elution, which contains GCT, was transferred onto an LD column, where GCT remained attached.…”
Section: Methodsmentioning
confidence: 99%
“…Accumulation of nitrite in cell supernatants was evaluated by Griess assay [ 33 , 34 ] as an indirect measure of NO production, as described in different models reported by Corbett and colleagues [ 31 ]. The Griess reagent is a 50 % v/v mixture of Reagent A (1 % w/v sulphanilamide) and Reagent B (0.1 % w/v naphthyl ethylenediamine dihydrochloride and 2.5 % w/v phosphoric acid).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown the low bioavailability of L-arginine and NO in P. falciparum malaria and positively correlated it with hemozoin levels [ 107 , 108 ]. In an in vitro study by Corbett et al [ 109 ], P. falciparum -induced hemozoin reduced the bioavailability of the amino acid L-arginine to iNOS, with a consequent reduction in NO synthesis in macrophages. Moreover, monocyte polarization during P. falciparum malaria infection reduced the NO bioavailability and increased the severity of the disease in children [ 103 ].…”
Section: Oxidative Stress In the Host Induced By Plasmodiummentioning
confidence: 99%
“…3.6 | Inhibitors of hemozoin formation P. falciparum hemozoin (HZ) is a by-product of hemoglobin digested from P. falciparum-infected red blood cells and released into the bloodstream after cell rupture (Corbett et al, 2018). CQ inhibits HZ formation and thus prevent detoxification of heme.…”
Section: Inductors Of Apoptosis Necrosis and Autophagymentioning
confidence: 99%